Peer Reviewers of JMH Volume 1 Number 3 February 2016 - Editorial Editorial Team (Universitas Kristen Maranatha, 2016)
We would like to thank our peer reviewers for the precious contributions in providing clinical,scientific, and methodological expertise for JMH Volume 1 Number 3. We appreciate everythoughtful review of submitted manuscripts and for making important contributions to improve thescientific quality of articles published in JMH. We listed the names in alphabetical order.Dr.dr.Agung Budi,Sp.BSdr. Amaylia Oehadian,Sp.PD-KHOMProf. Dr. Ambrosius Purba, dr.,MS.,AIFOdr.Cherry Azaria, M.Kesdr.Decky Gunawan,M.Kesdr. Djaja Rusmana, M.Si.dr Dono Pranoto, SpB., M.Kesdr. Frecillia Regina,Sp.A.,IBCLCDr. dr. Hana Ratnawati, M.Kes., PA(K)Ingrid S. Surono, PhDProf.dr. Jeanne A. Pawitan, MS, PhDdr. Justin Ginting, Sp.Raddr. Laella Kinghua Liana,Sp.PA,M.Kesdrg. Linda Sari Sembiring, Sp.KGADr. dr. Meilinah Hidayat, M.KesProf. Dr. dr. M. Nurhalim Shahibdrg. Ruslin,Sp.BM.,M.KesProf. Dr. dr. Susy Tjahjani, M.KesProf. dr. Wahyuni Lukita Atmadja, PhD.dr. Yenni Limyati, Sp.KFR.,M.Kes